Socialno izključevanje državnega uradnika Oskarja V. iz brkljarije slovenske državne uprave - Klajnšček, Ciril (Družboslovne razprave, 2004)
The article carries out the controversy of the prevailing concepts of social exclusion through the narrative representation of several years lasting social exclusion of the public servant Oscar V. from the trumpery of the Slovenian post-socialist state administration. It is shown how defective social participation, deprivileged situation, marginalization, lack of power and curtailed human dignity do not necessary correspond to social exclusion, which is usually considered as connected to the poverty, unemployment, bad living conditions, low degree of education, bad health status and limited access of deprived and marginal group to different life sources. We can see onthe concrete case how social exclusion - together with all the accompanying individual and family problems - can occur inside of the institutionalised state administration praxis. Narrative representation of social exclusion of public servant Oscar V. offers us the insight into the trumpery ("bricolage") of the institutionalised state administration. Such an inner gaze shows us the existing concepts of social exclusion as suitable to the actual state administration, but completely insufficient from the recent post-modern individual and social identity, individuality, integrity and subjectivity point of view
Keywords: družbena izolacija; družbena izključenost; država; state; institucije; državna uprava; zaposleni; identiteta; medosebni odnosi; delovni pogoji